Отбор и оценка некоторых гибридных форм хлопчатника на устойчивость к вилту - Мамедова, Н.Х.; Шихлинский, Г.М.; Мамедова, Р.Б. (Фактори експериментальної еволюції організмів, 2014)
Aims. The comparative phytopathological assessment of durability to Verticillium wilt diseases interspecific (G. hirsutum L. x G. hirsutum L.) and intraspecific (G. hirsutum L. x G. barbadense L.) cross of hybrids on artificial infection background was carried out in Absheron Research Base of Genetic Resources Institute of ANAS. Methods. On the phytopathological assessment of durability has been used 5-point system of F.M. Vaytenok. Results. During the study it was determined that the intraspecific cotton hybrids are more durable to verticillium wilt diseases, but not interspecific cross of hybrids. This can explain that G. barbadense L. cotton specie is more durable verticillium wilt diseases and exactly that is why G. barbadense L. specie takes part in creation of interspecific cotton of hybrids. Thus interspecific cross of hybrids indicators of durability to wilt diseases is higher. Conclusions. It’s possible to create new cotton sorts durable to wilt disease as well as highly technological fiber indicators completed in one genotype on the selection of cotton plant with widely using the long hybridization method. The selected forms from intraspecific hybrids which are durable and tolerant to wilt disease can be used as the beginning donor material on selection and creation of new cotton sorts.